2013
DOI: 10.1080/10447318.2013.839903
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Luminosity Contrast and Stimulus Duration on User Performance and Preference in a P300-Based Brain–Computer Interface

Abstract: Brain-computer interfaces (BCI) have potential to provide a new channel of communication and control for people with severe motor disabilities. Although many empirical studies exist, few have specifically evaluated the impact of contributing factors on user performance and perception in BCI applications, especially for users with motor disabilities. This article reports the effects of luminosity contrast and stimulus duration on user performance and usage preference in a P300-based BCI application, P300 Spelle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 41 publications
0
24
1
Order By: Relevance
“…Whether larger stimuli in a visual “single stimulus” paradigm elicit larger P300 amplitudes has not yet been systematically investigated. Li et al ( 2011 , 2014 ) investigated the effect of screen size and stimulus luminosity with a P300 BCI and found that a computer monitor elicited a larger P300 as compared to a cell phone display and reported a higher P300 with increased luminosity of the stimuli, the latter effect, however, was not significant. Similar P300 amplitudes were elicited by a visual oddball and a visual “single stimulus” paradigm (Mertens and Polich, 1997 ).…”
Section: Discussionmentioning
confidence: 99%
“…Whether larger stimuli in a visual “single stimulus” paradigm elicit larger P300 amplitudes has not yet been systematically investigated. Li et al ( 2011 , 2014 ) investigated the effect of screen size and stimulus luminosity with a P300 BCI and found that a computer monitor elicited a larger P300 as compared to a cell phone display and reported a higher P300 with increased luminosity of the stimuli, the latter effect, however, was not significant. Similar P300 amplitudes were elicited by a visual oddball and a visual “single stimulus” paradigm (Mertens and Polich, 1997 ).…”
Section: Discussionmentioning
confidence: 99%
“…The present study mainly focused on the effect of chromatic stimulus on the performance of an ERP-based BCI and discussed several related problems stated as follows: (1) the influence on the offline error trials brought by the layout and the relationship between the layout and adjacency distraction, (2) the availability of the conclusion (Li et al, 2014) applied to the present study that better performance (including higher accuracy, higher amplitude, and shorter latency) occurred in a high-luminosity contrast, and (3) the observation of the ERP components' waveforms in this work.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al (2014) investigated the effects of luminosity contrast on BCI performance. It was reported that higher classification accuracy was achieved by a high-luminosity contrast; higher amplitude and shorter latency of VEP P300 were also released by the high-luminosity contrast stimulus.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…III) The improvement of the BCI interface by studying its properties [19][20][21][22]. For P300-based BCI these lines of research have led to, inter varia, the introduction of language models for letter and word prediction [23][24][25], automatic pause detection [26], the use of faces for flashing symbols [24], the use of random groups or pseudo-random groups flashing instead of row-column flashing [27][28][29][30], the use of inter-stimulus intervals randomly drawn from an exponential distribution instead of constant [27], the dynamic stopping of flashing sequences [25,31], etc.…”
Section: I)mentioning
confidence: 99%